Obrazowanie sportu i rekreacji ruchowej w fabułach zabaw dydaktycznych - Winczewski, Piotr (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
This text is an extract from an extensive study into conveying culture through the storylines of didactic games. The presented material focuses on the issue of sport and physical recreation in its broader sense.In the report the results of the study have been presented, which included the storylines of 851 artistic activities and 851 musical and physical activities. To that end, textbooks intended for teachers have been referred to. Both kinds of games are being used while working with pupils of different ages in kindergartens and schools.In the study a set of several methods were used to reconstruct the transmission of didactic games. The storyline of each game was assessed as a whole on the basis of the modified technique of a case study. By this means a description of the world aimed at pupils has been provided.As shown, in the storylines of didactic games practically no themes of sport appear. Moreover, the physical recreation was relatively rarely presented to the pupils. That implies that the employment of the assessed games as a form of physical exertion promotion was not intended. Summing up, the study of methodical solutions overcoming the discussed problem has been suggested.